ANALISIS ARSITEKTUR SISTEM TROVE NATIONAL LIBRARY OF AUSTRALIA - Wishnu Hardi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
In 2008, the National Library of Australia initiated an ambitious project to create a "national discovery system" that connects all libraries in Australia. The project, called 'Trove', was launched in 2009 after being released in beta format for 6 months. Trove not only replaces the 8 collection service systems, but also provides a new experience to the public and researchers in and outside Australia by opening access to more extensive and varied contents. This paper discussed the background of the emergence of Trove, how the architecture of information technology systems is, content coverage, and what suggestions to further development of Trove are like.